The Oxford handbook of the Bible in Orthodox Christianity - Pentiuc, Eugen J. 1955- (Oxford Oxford University Press, Incorporated, 2022)
The Oxford Handbook of the Bible in Orthodox Christianity is designed to demonstrate how Orthodox Christian, namely, Eastern (Greek, Slavic, Romanian, Antiochene) and Oriental (Syriac, Coptic, Ethiopian and Armenian) communities have received, shaped, and interpreted the Christian Bible. The basic hallmark of Orthodox Christianity, a unique mix of strictness (tradition) and flexibility (innovation, modernity), is detectable at the level of text, canon, Scripture-Tradition relationship, and mostly in the area of biblical hermeneutics.
Description based on publisher supplied metadata and other sources
Keywords: Bible-Criticism, interpretation, etc; Orthodox Eastern Church-Doctrines; Theology, Doctrinal; Electronic books; Aufsatzsammlung